Lawyer Misconduct and Sanctions - Hunter, Richard J.; Shannon, John H. (Advances in Social Sciences Research Journal, 2023)
This article deals with issues relating to lawyer misconduct and possible litigation sanctions under Rule 11 of the Federal Rules of Civil Procedure relating to filing of a lawsuit that is frivolous or in “bad faith,” and to actions that may be taken against an attorney for misconduct under the Model Rules for Lawyer Disciplinary Enforcement, either in the course of representation of a client or more generally in the attorney’s practice of law. This is the fourth in a series of articles relating to the “lawyer client relationship.”*